Exogenous progesterone treatment during pregnancy for increasing milk production and growth of kids of Etawa grade goat - I-Ketut Sutama; I-G.M Budiarsana; Supriyati .; Hastono . (Indonesian Center for Animal Research and Development (ICARD), 2012)
Naturally, progesterone in ruminant is mainly produced by corpus luteum and it is reponsible for maintaining pregnancy, and affecting udder development and milk production. Exogenous progesterone treatment is expected to give similar positive effect on milk production as the endogenous progesterone does. Fourty mature Etawa grade (PE) does were synchronized for oestrus using Controlled Internal Drug Release (CIDR) followed by natural mating. Does then were treated with CIDR intravaginally, as a source of exogenous progesterone, at day 15-75 after mating (Group A), day 75-135 after mating (Group B), and without exogenous progesterone treatment (Control). Blood samples were taken before and after exogenous progesterone treatment for determination of progesterone concentrations. Soon after birth, kids were separated from their respective dams and they were milk fed through milk bottle. Feed consumption and milk production were measured daily, while bodyweight was measured forthnightly. Results showed that response of does following exogenous progesterone treatment was not expressed by an increase in progesterone concentration in the blood plasm. However, treatment group showed kid with birthweight of 10-13% higher compared to Control Group. In relation to milk yield, birthweight and pre-weaning growth of kids, the positive responses of exogenous progesterone treatment were not significant, though there was a substantial decrease (71.2%) in pre-weaning kid’s mortality. Key Words: Oestrous Synchronization, Progesterone, Milk, Etawa Goat